2010
DOI: 10.1016/j.joms.2009.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcoma of the Temporomandibular Joint: A Case Report and Review of the Literature

Abstract: You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions:(1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND license.(2) The integrity of the work and identification of the author, copyright owner, and publisher must be preserved in any copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…And open biopsy is definite to get final diagnosis. Histologically, our case showed Grade I and Nortjé et al [ 8 ], Morris et al [ 10 ], Nitzan et al [ 12 ], Sesenna et al [ 13 ], Garzino-Demo et al [ 17 ], and González-Pérez et al [ 18 ] reported low grade (Grade I) chondrosarcoma. Other reports had no grading information.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…And open biopsy is definite to get final diagnosis. Histologically, our case showed Grade I and Nortjé et al [ 8 ], Morris et al [ 10 ], Nitzan et al [ 12 ], Sesenna et al [ 13 ], Garzino-Demo et al [ 17 ], and González-Pérez et al [ 18 ] reported low grade (Grade I) chondrosarcoma. Other reports had no grading information.…”
Section: Discussionmentioning
confidence: 56%
“…From Garzino-Demo et al's review [ 17 ] and our case ( Table 1 ), the symptom duration of the 8 cases that had condyle resorption is 24, 8, 24, 72, 120, 3, 12, and 120 months. These periods were longer than the duration of the cases without condyle resorption.…”
Section: Discussionmentioning
confidence: 61%
“…Taking into account the overall biological behaviour of head and neck CHS, the most effective treatment modality for this neoplasia is aggressive surgery with wide en-bloc resection, ensuring that an adequate histologically clear margin is obtained, since residual disease is known to be an important cause of recurrence 9,19,20 . Irradiation and chemotherapy, although variably used in cases of CHS, do 208…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chondrosarcoma of the jaw is uncommon in the head and neck, but when present, it and primarily occurs at the anterior maxilla in the head and neck area or in the nasal cartilage. Chondrosarcoma in the temporomandibular joint (TMJ) area is exceptionally rare, and only 30 cases have been reported in the literature234567891011121314151617181920212223242526272829303132333435363738. Treatment of chondrosarcoma of the TMJ is often challenging and might be related to the presence of associated vital structures, which include the facial nerve, parotid gland, and the close proximity to the cranial base.…”
Section: Introductionmentioning
confidence: 99%